2021
DOI: 10.1002/ajmg.a.62144
|View full text |Cite
|
Sign up to set email alerts
|

Novel unconventional variants expand the allelic spectrum of OPHN1 gene

Abstract: Mutations in the OPHN1 gene cause a rare X‐linked recessive neurodevelopmental disorder characterized by intellectual disability, variably associated with cerebellar hypoplasia and distinctive facial appearance. In most of cases so far reported, the identified genomic variants involve the region encoding the central RhoGAP domain of the oligophrenin‐1 protein, and are predicted to result in a complete loss of function. By using a NGS‐based diagnostic approach, we identified three male and a female patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Numerous clinical studies have documented the association of the OPHN1 gene with neurodevelopmental disorders. To date, over 100 cases of intellectual developmental delay linked to mutations in the OPHN1 gene have been reported [ 22 ], encompassing more than 20 distinct mutation variants [ 23 ] known to contribute to conditions such as intellectual disability and autism(Supplementary Table 1 ). Billuart et al [ 11 ] identified a 1-bp deletion in the OPHN1 gene in a family case with X-linked syndromic intellectual developmental disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have documented the association of the OPHN1 gene with neurodevelopmental disorders. To date, over 100 cases of intellectual developmental delay linked to mutations in the OPHN1 gene have been reported [ 22 ], encompassing more than 20 distinct mutation variants [ 23 ] known to contribute to conditions such as intellectual disability and autism(Supplementary Table 1 ). Billuart et al [ 11 ] identified a 1-bp deletion in the OPHN1 gene in a family case with X-linked syndromic intellectual developmental disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, LOF mutations in OPHN1 cause syndromic XLID, in which ID is associated with epilepsy, ventriculomegaly, and cerebellar hypoplasia [ 167 , 168 , 169 ].…”
Section: Cytoskeleton Functions In Neuronal Developmentmentioning
confidence: 99%